2013
DOI: 10.1007/978-3-642-40790-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Game Design for All: The Example of Hammer and Planks

Abstract: Last years have seen a growing interest on the Serious Games topic-and in particular on Games for Health-from both scientific and industrial communities. However not only the effectiveness of this kind of games is not yet demonstrated but the distribution and adoption of these games from the normal public is still very low. In this paper we present a design strategy we adopted in on the occasion of the development of a game for hemiplegic rehabilitation named "Hammer and Planks". This game strategy allowed us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…33,34 Using off-the-shelf video games has provided promising results in stroke, 33 Parkinson's disease, 35 and in the elderly. 36,37 Moreover, dedicated video games have been developed with the purpose of treating patients with neurological disorders, 38,39 for movement rehabilitation 40,41 and cognitive rehabilitation, 42 for example, in patients with Parkinson's disease, 15 traumatic brain injury, 43 stroke, 44 and dementia. 45 One of the advantages of serious games is to allow for at-home training, without the presence of a therapist.…”
Section: Serious Games For Healthmentioning
confidence: 99%
“…33,34 Using off-the-shelf video games has provided promising results in stroke, 33 Parkinson's disease, 35 and in the elderly. 36,37 Moreover, dedicated video games have been developed with the purpose of treating patients with neurological disorders, 38,39 for movement rehabilitation 40,41 and cognitive rehabilitation, 42 for example, in patients with Parkinson's disease, 15 traumatic brain injury, 43 stroke, 44 and dementia. 45 One of the advantages of serious games is to allow for at-home training, without the presence of a therapist.…”
Section: Serious Games For Healthmentioning
confidence: 99%
“…Developing an original exergame to support physical education or to help patients to recover motor abilities using gaming is not new [15][16][17][18]. Lin et al [19], inspired by the Tamagotchi virtual-friend concept designed a pervasive game called "Fish'n Steps" to encourage people to walk.…”
Section: Creating An Original Game Universementioning
confidence: 99%
“…The goal of Hammer and Planks game is to kill all the enemies while avoiding any attack from the enemies and obstacles [5]. Along the way, players can also catch bonuses to increase their score.…”
Section: Game Event Structurementioning
confidence: 99%
“…We identified that two types of distances need to be considered: (i) how different are the sections in terms of the proportion of the event types in each section (ii) how different are the sections in terms of the evolution of each event type throughout the sessions. For instance, with the (i) approach, s 2 and s 3 are similar because the triplets of each session are proportional ([20,40,10] is proportional to [10,20,5]…”
Section: Distance Calculationmentioning
confidence: 99%